FARMERS' KNOWLEDGE AND INCENTIVE IN REPORTING INFECTIOUS ANIMAL DISEASE: THE CASE OF AFRICAN SWINE FEVER IN MADAGASCAR - T. N. Randrianantoandro; S. Kubota; H. Kono (Journal of Animal and Plant Sciences, 2018)
One issue in the control of infectious animal disease is adverse selection, meaning farmers have information about the health status of their animals during an outbreak, but are unwilling to report it to the government. The objectives of our study are, first, to elicit farmers’ knowledge about African swine fever (ASF) and, second, determine farmers’ willingness to accept (WTA) compensation as an incentive for reporting ASF cases. To evaluate their knowledge about the disease, 201 pig farmers were interviewed using questions related to ASF. The contingent valuation (CV) technique was used to estimate their WTA compensation for culled pigs. The results show that the majority of the farmers answered questions regarding ASF correctly. The CV results also show that, as compensation increases, more farmers are willing to report ASF cases. However, the probability of reporting depends on certain farm-related characteristics, namely, farmers’ knowledge about ASF, administration of the classical swine fever vaccine, and experiences with ASF. The results indicate that providing adequate financial compensation is important for incentivizing the reporting of ASF outbreaks. Even so, it is necessary to also conduct an awareness campaign on ASF’s economic impact to prevent farmers who know that ASF is not harmful to human health from rejecting compensation. In addition, farmers’ knowledge about ASF transmission should be improved.
Keywords: African swine fever; farmers’ knowledge; Madagascar; willingness to accept compensation